SINTESIS MATERIAL SILIKA MESOPORI SBA-15 DARI ABU DAUN BAMBU PETUNG (Dendrocalamus asper (Schult.) Backer ex Heyne) - Anke Rienhar Saputra; Alimuddin Alimuddin; R.R. Dirgarini Julia N. (PROSIDING SEMINAR KIMIA, 2017)
A study on the synthesis and characterization of mesoporous silicas SBA-15 (Santa Barbara Acid 15) from bamboo leaf ash. SBA-15 from bamboo leaf ash leaves was synthesized by modification of the microemulsion template method. SBA-15 was characterized by N2 adsorption/desorption analyzer, SAXS (Small Angel X-Ray Difraction), FTIR (Fourier Transform Infrared) and SEM (Scanning Electron Microscopy). N2 adsorption/desorption analyses showed that SBA-15 has type IV isotherms, with H1 type hysteresis which was a characteristic of mesoporous materials. ​​SBA-15 from bamboo leaf ash has surface are (calculated by BET method) of 698 m2 / g, pore volume of 0.81 cm3 /g and pore diameter of 4.66 nm. In the difractogram appeared 3 typical peaks of SBA-15 between 0.5 - 5o 2θ with miller indices (100), (110) and (200), respectively. The FTIR spectrum showed peaks from siloxane (Si-O-Si) and hydroxyl groups (-OH). The SEM pictures showed that the morphology of SBA-15 was a combination of platelets and spheres with the average particle size of 0.5 μm. Kata kunci: Bamboo leaf Ash, SBA – 15